(untitled) (Contexto (Universidad de los Llanos), 2024)
The Universidad de los Llanos is a place that vibrates with the energy of its community, and proof of this is how the sports venues are filled with activity and enthusiasm, with a wide variety of sports and cultural activities that reflect the diversity and passion of the university community. From Monday to Friday, at noon, on the Barcelona, ​​San Antonio and Boquemonte (Granada) campuses, you can see students, teachers and administrators training or learning new skills, which awaken the competitiveness and sportsmanship of those who participate.